HISTORIOGRAPHY OF PROBLEM OF USING INFORMATION RESOURCES IN PRACTICE OF HISTORY TEACHING (Educological discourse, 2015)
This paper discusses the implementation at the turn of the nineteenth and twentieth centuries, the method using information resources in teaching history in local schools. The author analyzes the views of contemporary trainers and dydakta on the implementation of real and abstract teaching methods, the use of readers, which made it possible to increase participation of students from forming abilities to use information resources. The paper presents a scientific novelty identify effective implementation of the author's procedures during this period. Experience has outlined the prospects for the use and development in the educational process in secondary schools.